Development of the Art of Reading the Qur'an by Students of the Asy-Syifa Qur'an House, Cengkeh Turi Village, North Binjai District, Binjai City - Habibi, Rozaq; Sahar, Zaidun (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to determine the development of the art of reading the Qur'an of students at the Asy-Syifa Al-Qur'an House in Cengkeh Turi Village, North Binjai District, Binjai City, the learning methods used, and the learning outcomes achieved. This study uses a qualitative approach with case studies, carried out in natural conditions through interviews, observations, and documentation. The results of the study indicate that the development is carried out routinely according to the established schedule, with a focus on improving the ability to read the Qur'an according to the rules of tajwid and the development of the art of reading Tartil and Tilawatil Qur'an until they are ready to compete in the MTQ event. The learning methods used include demonstration and imitation, intensive drill and practice, individual approaches, periodic evaluations, and the use of technology such as sound recordings and murottal applications. The results of the development show that students are able to read the Qur'an with correct tajwid, master the maqam tilawah, dare to appear in public, excel in MTQ competitions, and the growth of a culture of love for the Qur'an through the beauty of reading.